Influence of Dietary Factors on Helicobacter pylori and CagA Seroprevalence in Bulgaria - Daniel Yordanov; Lyudmila Boyanova; Rumyana Markovska; Juliana Ilieva; Nikolay Andreev; Galina Gergova; Ivan Mitov (Gastroenterology Research and Practice)
The aim of this study was to assess the association between some dietary factors and prevalence of H. pylori infection or strain virulence in 294 adult asymptomatic blood donors. Methods. Seroprevalence was evaluated using ELISA. Logistic regression was used. Results. Anti-H. pylori IgG prevalence was 72.4%, and CagA IgG seroprevalence was 49.3%. In the multivariate analyses, the frequent (>5 days per week) honey consumption was associated with both reduced H. pylori seroprevalence OR, 0.68 with 95% confidence interval (CI), 0.473–0.967 and reduced CagA IgG seroprevalence OR, 0.65 with 95% CI, 0.486–0859. Frequent (>5 days per week) yoghurt consumption also was associated with lower H. pylori virulence of the strains (CagA IgG OR, 0.56 with 95% CI, 0.341–0.921). Smoking and consumption of the other dietary factors resulted in no significant differences in the prevalence of H. pylori IgG and CagA IgG within the subject groups. Conclusion. To the best of our knowledge, this is the first report revealing reverse associations between honey or yoghurt consumption and CagA IgG prevalence as well as between frequent honey consumption and lower prevalence of the H. pylori infection. Regular honey and yoghurt consumption can be of value as a supplement in the control of H. pylori therapy.